Influence of Human Resource Development And Service Quality On Work Productivity Class II Land Transportation Management Center In South Sumatra - Julaini, Julaini; Akila, Akila; Mafra, Nisa' Ulul (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose : This study analyzes the effect of human resource development and service quality on work productivity at the Class II Land Transportation Management Center of South Sumatra. Methodology: The method used is a quantitative approach with associative research type, sampling technique using saturated sampling method involving 45 employees. Results: The results of the study identified that human resource development and service quality have a significant influence on work productivity, both partially and simultaneously. Findings: This findings shows that increasing employee competency and optimal service can encourage higher work productivity. Originality: Human resource development, including training, career development and competency improvement, is proven  to increase employee effectiveness. Meanwhile, good service quality creates job satisfaction and a conducive work environment, which has a positive impact on employee performance. Conclusion: Institutional management is advised to continue implementing training program development, performance evaluation, and service quality improvement as a strategic step in improving overall work productivity. Paper Type: Research Article.